Muslim youth: challenges, opportunities and expectations - Ahmad, Fauzia; Seddon, Mohammed Sidiq (Continuum International Pub. Group, 2011)
Introduction / Mohammad S. Seddon & Fauzia Ahmad -- Muslim youth : negotiating local and global contexts -- The phenomenon of dual nihilism among the British Muslim youth of Bradford / Saeed a. Khan -- Why is Hizb-ut Tahrir influential in Britain and Uzbekistan but not in Turkey and Egypt? / Ihsan Yilmaz -- Identity and belonging -- Muslim migrant youth: descriptive factors related to acculturation and psychosocial adaptation / M. Taqi Tirmazi, Altaf Husain, Fatima Mirza & Tasanee R. Walsh -- Religion, language or ethnicity? hybridised youth identity among the Afghan Ismaili community in Germany / Yahia Baiza -- Turning to my religion / M. G. Khan -- Education and new media -- Growing up under lockdown or educational pioneers? Challenging stereotypes of British Muslim women in higher education / Fauzia Ahmad -- Muslim youth at university: a critical examination of the British higher education system / Seyfeddin Kara -- Muslim youth and citizenship education: idealism, islam and prospects for successful citizenship education / Nader al-Refai & Christopher Bagley -- Methodologies of engaging -- activity and alterity: youth work with Muslim girls / Gill Cressey -- Youth work and islam: a growing tradition / Brian Belton -- Training muslim youths to be khateebs arif fitzsimon -- Engaging with young muslims: some paradigms from the Quran and Sunnah Mohammad S. Seddon.